2009
DOI: 10.1371/journal.pone.0007930
|View full text |Cite
|
Sign up to set email alerts
|

Lrp4, a Novel Receptor for Dickkopf 1 and Sclerostin, Is Expressed by Osteoblasts and Regulates Bone Growth and Turnover In Vivo

Abstract: Lrp4 is a multifunctional member of the low density lipoprotein-receptor gene family and a modulator of extracellular cell signaling pathways in development. For example, Lrp4 binds Wise, a secreted Wnt modulator and BMP antagonist. Lrp4 shares structural elements within the extracellular ligand binding domain with Lrp5 and Lrp6, two established Wnt co-receptors with important roles in osteogenesis. Sclerostin is a potent osteocyte secreted inhibitor of bone formation that directly binds Lrp5 and Lrp6 and modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
178
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 61 publications
4
178
1
2
Order By: Relevance
“…Sclerostin, the product of the SOST gene expressed by mature osteocytes, is a physiological negative modulator of bone formation (49,50). Sclerostin binds only weakly to BMPs and acts by antagonizing Wnt binding to LRP4-6 co-receptors (51,52). The pre-clinical observation that loss-of-function mutation of sclerostin results in increased bone formation and bone mass (53) led to the interesting concept that targeting sclerostin may increase bone formation in vivo (54).…”
Section: Therapies In Pipelinementioning
confidence: 99%
“…Sclerostin, the product of the SOST gene expressed by mature osteocytes, is a physiological negative modulator of bone formation (49,50). Sclerostin binds only weakly to BMPs and acts by antagonizing Wnt binding to LRP4-6 co-receptors (51,52). The pre-clinical observation that loss-of-function mutation of sclerostin results in increased bone formation and bone mass (53) led to the interesting concept that targeting sclerostin may increase bone formation in vivo (54).…”
Section: Therapies In Pipelinementioning
confidence: 99%
“…It is a potent Wnt antagonist [2], vital for head and limb development [2][3]. Dkk1 binds to low-density lipoprotein related proteins 4, 5 and 6 (LRP4/5/6) [4][5][6][7]. The exact mode of action is unclear, but it appears that Dkk1 directly competes with Wnt-ligand in binding to LRP6 [8] thus antagonizing Wnt signalling [9] and increasing β-catenin degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of hypomorphic (partial loss-offunction) LRP4 alleles in mice showed that LRP4 appears to play a role in achieving and/or maintaining normal bone mass. (49) This, coupled with recent exciting data demonstrating that certain missense mutations in LRP4 cause increased bone mineral density in humans, (50) strongly suggests that sclerostin interacts with LRP4 in vivo.…”
mentioning
confidence: 98%
“…Recently, it has been reported that sclerostin binds to LRP4, a singletransmembrane protein related to LRP5 and LRP6, and, additionally, that LRP4 is expressed in bone by osteoblasts and osteocytes. (48,49) Knockdown of LRP4 expression in cell culture was found to block sclerostin's inhibitory activity on Wnt signaling and on in vitro mineralization. (48) Thus in these in vitro systems, sclerostin's activity was shown to depend on the presence of LRP4.…”
mentioning
confidence: 99%